Avaliação da eficácia da ultra-sonografia anorretal tridimensional dinâmica no diagnóstico de animus em mulheres com evacuação obstruída comparando com a eletromanometria anorretal - Lima, Doryane Maria dos Reis (2006)
Approximately half of the constipated patients shows symptoms of obstructed defecation and anismus is one of the main causes. The aim of this study is to demonstrate a new technique using dynamic three-dimensional anorectal ultrasonography for diagnosis of anismus and compare the results with anorectal manometry. This prospective and comparative study was carried out by seventy women with symptoms of obstructed defecation selected from the Colorectal Unit of the Walter Cantídio University Hospital of the Federal University of the Ceará, between may 2005 and august 2006. The mean age was 48 years old (range 23 – 79). All the patients were initially submitted to anorectal manometry and then, depending on the results, separated into two groups. Group I, consisting of forty patients with normal results and presenting anal striated muscles relaxation during straining and group II with the thirty remaining patients with diagnosis of anismus. Subsequently, the patients from both groups were submitted to dynamic three-dimensional anorectal ultrasonography. The method consisted of two automatic scans at rest and during straining. Then, both images were analyzed in the axial and longitudinal planes in order to identify the PR movements. The technique consisted to determine an angle between a line traced parallel to the internal edge of the PR ( 1.5cm ) with another vertical and perpendicular line with the anal canal axis. This angle is calculated at rest and during straining and the average resting angle size was 88.37 º ± 4.05 in group I and 89.13 º ± 5.73 in group II, without significant difference between them ( p=0.51 ). The mean angle size during straining was of 98.19 º ± 1.18 in group I and 84.94 º ± 1.31 in group II, showing significant statistical difference ( p<0.001 ). Thus, the dynamic three-dimensional anorectal ultrasonography showed the same results of the anal manometry in 92.86 % of the patients regarding anismus diagnosis in patients with symptoms of obstructed defecation. As a conclusion, the dynamic ultrasonography technique showed to be considered efficient for anismus diagnosis, with the advantage to simultaneously demonstrate the anatomical conformation of the anal canal.